2004
DOI: 10.1021/jm0499110
|View full text |Cite
|
Sign up to set email alerts
|

Improved Structure−Activity Relationship Analysis of HIV-1 Protease Inhibitors Using Interaction Kinetic Data

Abstract: Despite the availability of large amounts of data for HIV-protease inhibitors and their effectiveness with wild type and resistant enzyme, there is limited knowledge about how this and other information can be systematically applied to the development of new antiviral compounds. To identify in vitro parameters that correlate with the efficacy of HIV inhibitors in cell culture, the relationships between inhibition, interaction kinetic, and cell culture parameters for HIV-1 protease inhibitors were analyzed. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…The PIs show differential accumulations within lymphoblastoid cell lines (21) and peripheral blood mononuclear cells of virologically suppressed patients in vivo, with NFV and SQV accumulations higher than those of LPV and RTV (24). Thus, the rank order effects of the different PIs on neutrophil functions and apoptosis shown in our study are similar to their reported cell culture efficacies (which represent the concentrations of inhibitor that result in 50% inhibition of HIV type 1 replication [47]) and to their rank order for cellular accumulation (18,24). The significant recovery of neutrophil functions reported after the treatment of HIV patients (35) raises the possibility that the main in vivo effect of the PIs on neutrophils is in reducing the number of functionally defective apoptotic cells (53).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The PIs show differential accumulations within lymphoblastoid cell lines (21) and peripheral blood mononuclear cells of virologically suppressed patients in vivo, with NFV and SQV accumulations higher than those of LPV and RTV (24). Thus, the rank order effects of the different PIs on neutrophil functions and apoptosis shown in our study are similar to their reported cell culture efficacies (which represent the concentrations of inhibitor that result in 50% inhibition of HIV type 1 replication [47]) and to their rank order for cellular accumulation (18,24). The significant recovery of neutrophil functions reported after the treatment of HIV patients (35) raises the possibility that the main in vivo effect of the PIs on neutrophils is in reducing the number of functionally defective apoptotic cells (53).…”
Section: Discussionsupporting
confidence: 83%
“…The PIs act by blocking the HIV aspartyl protease, a viral enzyme that cleaves the HIV Gag and Gag-Pol polyprotein backbone, thereby interrupting the viral life cycle. These PIs have been reported to have different affinities, inhibition constants, physiochemical properties, and cell culture efficacies (16,47). The highest cell culture efficacies were detected for SQV and NFV and the lowest for APV.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of [I]/K i was performed with two different K i values for RTV: the highest K i reported in the literature (55 pM) (17), as the K i values for all PIs were evaluated in the same work, and a mean K i calculated from different works reported in the literature (37.5 pM) (18)(19)(20). Moreover, once the observed [I]/K i values for RTV and for the concomitant PI in each sample were obtained, the ratio between these two values was calculated (RTV 1/concomitant PI 1).…”
Section: Patients and Inclusion Criteriamentioning
confidence: 99%
“…12,13 They act as antibiotics, herbicides, 14 inhibitors of the enzymes renin, EPSP synthase and HIV protease. 15,16 In addition a-amino phosphonates have broad applications due to their antifungal 17 and antibacterial activities. 18 Various synthetic approaches have been reported for the synthesis of a-amino phosphonates, among which the most convenient are the Kabachnik-Fields 19 31 and Mg(ClO 4 ) 32 as well as chiral catalysts 33,34 have been examined.…”
mentioning
confidence: 99%